Gender and innovation processes in maize-based systems - Petesch, Patti; Badstue, Lone B.; Williams, G.; Farnworth, Cathy Rozel; Umantseva, A. (International Maize and Wheat Improvement Center, 2017)
This MAIZE report offers a panorama of the gender dimensions of local agricultural innovation processes in the context of maize-based farming systems and livelihoods.